2008
DOI: 10.1089/cbr.2008.0510
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of FDG Single-Photon Emission Computed Tomography: Computed Tomography in the Diagnosis of Head and Neck Cancers and Study of Its Mechanism

Abstract: (18)F-FDG SPECT-CT can be as a prospective tool that can judge the malignancy or benignity of head and neck tumor, stage and classify the tumor, distinguish recurrence or necrosis or fibrosis of the tumor after treatment by surgery or radiotherapy, and detect unknown primary tumor. Glut-1 may largely mediate basal glucose transport in HNC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Warburg effect is that the higher glucose metabolic rate in malignant tumor cells as compared to their nonmalignant counterparts even in aerobic glycolysis. Many studies 4-7, including ours 8, have revealed that glucose transporter-1(GLUT-1) plays a significant role in malignant glucose metabolism and that it might contribute to the increased FDG uptake.…”
Section: Introductionmentioning
confidence: 97%
“…Warburg effect is that the higher glucose metabolic rate in malignant tumor cells as compared to their nonmalignant counterparts even in aerobic glycolysis. Many studies 4-7, including ours 8, have revealed that glucose transporter-1(GLUT-1) plays a significant role in malignant glucose metabolism and that it might contribute to the increased FDG uptake.…”
Section: Introductionmentioning
confidence: 97%
“…High FDG uptake by human carcinomas is also associated with a poor prognosis (9,19). Our previous study identified that the FDG uptake detected by single photon emission CT in head and neck cancers was associated with increased Glut-1 expression (20). Our recent preliminary study also revealed that the maximum standardized uptake value (SUV max ) of PET/CT in the cervical lymph nodes predicted cervical metastasis of a carcinoma from an unknown primary tumor (3).…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms of 18 F-FDG uptake have been proposed for accelerated glucose use in growing tumors and in transformed and malignant cells. These include passive diffusion, Na + -dependent glucose transport and facilitative glucose transporters (GLUTs) (10), with GLUTs considered to be the most significant mechanism for enhancing glucose influx into cells. GLUTs are membrane proteins that facilitate the transport of glucose across cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The human genes encoding these proteins are named GLUT-l to -5 and GLUT-7 to -13; GLUT-6 and -14 are now known to be pseudogenes. Of the 14 isoforms, GLUT-1 appears to be the most ubiquitously distributed (10,12,13). Increased GLUT-1 levels and glucose uptake correlate with increased cellular growth and proliferation (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation